Editorial Foreword: Challenging Academic Participation - Schmidt Nielsen, Ann-Katrine; Hendry, Natalie Ann; Uldbjerg Mortensen, Signe (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
This issue contributes to the growing criticisms of and challenges to participatory methods and cultural participation by focusing on ‘academic participation’. By academic participation, we refer to the use of participatory methodologies in academic research, but we also aim to expand the term by including reflections on the modes and conditions of taking part — willingly and unwillingly — in academic systems and institutions as such. The articles of this issue invite the reader to reconsider what and how participation looks like in the academy. Taken together, they suggest that we might need to broaden how we understand, apply and critique participation in academic research: from the participatory methods applied in specific research projects, to how we might foster a more participatory academic system that rejects the current individualization, financialization, and exploitation at play.